2017
DOI: 10.1097/md.0000000000008017
|View full text |Cite|
|
Sign up to set email alerts
|

Successful management of octreotide-insensitive thyrotropin-secreting pituitary adenoma with bromocriptine and surgery

Abstract: Attention should be paid to the role of dopamine agonists such as bromocriptine and cabergoline as adjuvant therapy for TSHomas that are insensitive to traditional medical treatment by somatostatin analogs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
6
0
1
Order By: Relevance
“…Here, bromocriptine combined with TEM was used as a basic treatment for rPA after tumor resection. Bromocriptine, a derivative of ergometrine, is a specific allosteric hypothalamic and pituitary dopamine receptor agonist that acts directly on the adenohypophysis to inhibit PRL secretion and facilitate GH release [ 15 ]. It has been reported that bromocriptine is effective in the treatment of hyperprolactinemia with prolactinoma, as bromocriptine effectively regulates prolactin, reestablishes gonadal function, and reduces tumor volume [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Here, bromocriptine combined with TEM was used as a basic treatment for rPA after tumor resection. Bromocriptine, a derivative of ergometrine, is a specific allosteric hypothalamic and pituitary dopamine receptor agonist that acts directly on the adenohypophysis to inhibit PRL secretion and facilitate GH release [ 15 ]. It has been reported that bromocriptine is effective in the treatment of hyperprolactinemia with prolactinoma, as bromocriptine effectively regulates prolactin, reestablishes gonadal function, and reduces tumor volume [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…DAs may be used as a second‐line medical therapy to facilitate euthyroid states preoperatively if SST agonists are not tolerated, and can also be used to treat TSHomas if surgery is contraindicated, although the reported benefits have been modest. The successful preoperative use of bromocriptine in a case of a TSHoma not responsive to SST analogues has been reported, 109 and there are scattered case reports of hormonal control achieved with DAs when surgery is contraindicated 110,111 . However, in a case series by Socin and colleagues describing the use of DAs in 7 TSHoma patients, a response was only observed in a single subject whose tumour cosecreted prolactin 104 .…”
Section: Dopamine Agonists For the Treatment Of Thyroid Stimulating H...mentioning
confidence: 99%
“…88 Dopamine agonists may be used as second-line medical therapy to facilitate euthyroid states pre-operatively if somatostatin agonists are not tolerated, and can also be used to treat TSHomas if surgery is contraindicated, although the reported benefits have been modest. The successful pre-operative use of bromocriptine in a case of a TSHoma not responsive to somatostatin analogs has been reported, 98 and there are scattered case reports of hormonal control achieved with dopamine agonists when surgery is contraindicated. 99,100 However, in a case series by Socin and colleagues describing the use of dopamine agonists in seven TSHoma patients, a response was only observed in a single subject whose tumor cosecreted prolactin.…”
Section: Dopamine Agonist For the Treatment Of Tsh-secreting Adenomasmentioning
confidence: 99%